Knowledge and opinion in Aristotle (Diametros, 2011)
In the article I examine Aristotle’s distinction between knowledge and opinion. I first consider Aristotle’s notion of rational intuition in the light of the commentaries of Ross and Apostle. Next, I turn to the distinction between opinion and knowledge in Aristotle’s texts and in the commentaries of Aquinas and Barnes. I conclude that the distinction is complex, including a number of factors, some objective, others subjective. Aristotle believes that the object of knowledge must be objectively true and necessary; it must subjectively be seen as necessary; the true cause has to be known; and the necessity of the causal connection must be perceived. The most important criterion for knowledge is objective necessity. If any of the aforementioned criteria is not satisfied, there can according to him be at most true opinion.